DATE OF HATE IN SOCIAL MEDIA (FACEBOOK) ACCORDING TO LAW NUMBER 19 OF 2016 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS - Yolanda, Nina (Awang Long Law Review, 2021)
Hate Speech is "The act of communication carried out by an individual or group in the form of provocation, incitement, or insult to other individuals or groups in terms of various aspects such as race, color, gender, disability, sexual orientation, citizenship and so on. Other problems in this thesis, namely: 1. Forms of Hate Speech on Social Media. 2. Government authority for the operation of Electronic Systems that violate the law. Hate Speech (Hate Speech) on social media (Facebook), namely forms of Hate Speech, namely insulting, defamation, defamation, unpleasant actions, provoking, inciting, spreading fake news.